Punctuation Marks and Signs of Cessation in Qur`an: a comparative study - Abdur-Rasheed Mahmoud-Mukadam (UIR Press, 2019)
The subject of punctuation in Arabic writing may be one of the topics in which there was a great deal of writing. However, the close look at this paper reveals that there are some new things that the researcher is interested in highlighting in this article. To clarify positions in the Holy Quran. And that some contemporary writers do not take into account the status of these signs and interesting situation in the appropriate places, but they refuse to take into account behind their appearance when writing Arabic became randomly writing, Based on the above, the researcher can shed light on the importance of these punctuation marks and indicate the relationship between them and the signs of the Qur`anic cessation, which does not mean the use of the first place with The existence of the connection and kinship between them; because the writing of Qur`an is descriptive, it could never be treated in the places of cessation and tone as usual treatment of the normal writing.